Extracurricular Coloring Activities to Develop Creativity of Class V Students of Sdn 1 Nagri Tengah - Wina Mustikaati; Andhini Oktafrina; Hanny Rahmawati; Ica Nurlaela; Pani Herlina (al-Afkar, Journal For Islamic Studies, 2025)
Creativity is an important aspect in child development. This article discusses the importance of coloring extracurricular activities in developing the creativity of grade V students at SDN 1 Nagri Tengah. This article uses qualitative research methods with observation techniques on class V students of SDN 1 Nagri Tengah. The research was conducted involving 30 5th grade students who were active in coloring extracurricular activities in several meetings. Data collection methods include observation, interviews and portfolio analysis. The research results showed a significant increase in students' creativity, especially in terms of color selection, depiction techniques, and self-expression. This activity also helps students improve concentration and perseverance. This research provides a deeper understanding of the importance of coloring extracurricular activities in basic education to facilitate the development of children's creativity.